2018
DOI: 10.1029/2018gl079873
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Changes in Arctic Cloud Phase Due to Long‐Range Pollution Transport

Abstract: Reduced precipitation rates allow pollution within air parcels from midlatitudes to reach the Arctic without being scavenged. We use satellite and tracer transport model data sets to evaluate the degree of supercooling required for 50% of a chosen ensemble of low-level clouds to be in the ice phase for a given meteorological regime. Our results suggest that smaller cloud droplet effective radii are related to higher required amounts of supercooling but that, overall, pollution plumes from fossil fuel combustio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 85 publications
(160 reference statements)
7
25
0
Order By: Relevance
“…T50 increases from 26 ±1C for reLiq in a bin between 5 and 9 normalμm to 20 ±1C for reLiq in a bin between 21 and 25 normalμm. Higher values of reLiq are associated with higher T50 in line with previous studies (e.g., Coopman et al, ; Rangno & Hobbs, ; Rosenfeld et al, ). We further classified the data by reLiq to retrieve T50 binned according to latitude, ω700, and SH700.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…T50 increases from 26 ±1C for reLiq in a bin between 5 and 9 normalμm to 20 ±1C for reLiq in a bin between 21 and 25 normalμm. Higher values of reLiq are associated with higher T50 in line with previous studies (e.g., Coopman et al, ; Rangno & Hobbs, ; Rosenfeld et al, ). We further classified the data by reLiq to retrieve T50 binned according to latitude, ω700, and SH700.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that Antarctic clouds glaciate at lower temperature than other clouds because Antarctic clouds are in contact with lower concentrations of aerosols that may serve as potential ice nuclei and facilitate phase transitions. Coopman et al (2018) studied the phase transition of Arctic clouds for different regimes of pollution from fossil fuel combustion and retrieved a glaciation temperature of about −20 • C; the presence of pollution increases the glaciation temperature up to 4 • C. Similarly, Filioglou et al (2019) have shown from CALIPSO and CloudSat measurements that high aerosol loadings increase the glaciation temperature by 10 • C in presence of dust and continental aerosols in the Arctic. We suggest that larger liquid cloud droplets are associated with higher glaciation temperatures because they aid secondary ice nucleation (Rosenfeld et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Between −38°C and 0°C, clouds can be either liquid, ice or a mixture of the two phases and different parameters influence the phase transition: For example, aerosols can act as ice nuclei, while large cloud droplets are more prone to secondary ice production (Rosenfeld et al, 2011); both examples potentially increase the glaciation temperature ( T g ). Parameters, such as the cloud droplet size and aerosol concentration, can be correlated or anti‐correlated with each other, and it is therefore difficult to disentangle their respective effect on T g (Coopman et al, 2018; Gryspeerdt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cloud droplets freeze homogeneously at −37 • C but for temperatures between −37 and 0 • C, supercooled cloud droplets and ice crystals can be observed (Cober et al, 2001;Rauber & Tokay, 1991). The temperature of glaciation of a cloud depends on different parameters, such as cloud altitudes, surface types, cloud droplet sizes, or pollution concentration (Carro-Calvo et al, 2016;Coopman et al, 2018;Rangno & Hobbs, 2001;Rosenfeld et al, 2011;Zamora et al, 2018). Clouds can therefore be composed of either only cloud droplets-referred to as liquid clouds-or only ice crystals-referred to as ice clouds-or a combination of supercooled liquid droplets and ice crystals-referred to as mixed-phase clouds (Korolev et al, 2017).…”
Section: Introductionmentioning
confidence: 99%